Advances in Research Using the C-SPAN Archives - Browning, Robert X. (The C-SPAN Archives, 2016)
This book is a guide to the latest research using the C-SPAN Archives. In this book, nine authors present original work using the video archives to study presidential debates, public opinion and Congress, analysis of the Violence Against Women Act and the Great Lakes freshwater legislation, as well as President Clinton's grand jury testimony. The C-SPAN Archives contain over 220,000 hours of first run digital video of the nation's public affairs record. These and other essays serve as guides for scholars who want to explore the research potential of this robust public policy and communications resource.